A study on energy expenditure in different running distances through physiological indicators - Saleh, Ahmed Yakdhan; Aga, Mohammed Twfeq Al Husaen (International Journal of Innovative Research and Scientific Studies, 2025)
This study aimed to investigate the physiological variables and total energy expenditure during a race (100m, 400m, 3000m). A portable gas analyzer (K5) was used to measure oxygen uptake (VO₂) of eleven specially trained runners competing on an outdoor track. The tests included (1) 100m, 400m, and 3000m. Blood lactate was analyzed at rest and at 3, 5, and 7 minutes after the end of the two races. All results in the 100m race showed no significant correlation between energy expenditure and physiological variables if they were all ≥ 0.05. While in the 400m race, there was a significant correlation between total energy expenditure and each of the factors (RF, VT, VE, VO₂, VCO₂, VO₂ ml·kg⁻¹·min⁻¹, and MET), where the significance value was ≤ 0.05, while it did not reach the significance value for RQ and HR as the significance values were ≥ 0.05. A significant correlation was found in the 3000m race, where the significance value was ≤ 0.05 between energy expenditure and each of VT, VE, VO₂, VCO₂, RQ, VO₂ ml·kg⁻¹·min⁻¹, and MET, while it did not reach the significance value for RF and HR. In conclusion, the duration and type of activity dictate metabolic dominance (aerobic vs. anaerobic) and influence the relationship between physiological variables and energy expenditure. Aerobic variables (VO₂, VE, VCO₂) are significant for longer activities (>3 minutes), whereas their relevance diminishes in shorter activities. The results have transformative implications for sports science and clinical practice, enabling tailored strategies to optimize athletic performance and metabolic health across diverse athletes.